An optimal scheduling algorithm for DASH video streaming over variable bit rate networks. (17th June 2020) - Chang, Shin-Hung; Wang, Kuan-Jen; Ho, Jan-Ming
With the rapid increase of network bandwidth, it becomes popular for people to watch video over the internet. To cope with dynamic and heterogeneous network condition, commercial service providers use DASH streaming technology to serve contents to their users. Under the limited bandwidth constraint, previous scheduling algorithms usually arrange as many as possible highest-resolution segments in a DASH streaming service. However, scheduling the most highest-resolution segments will lead to arrange the most lowest-resolution segments in this streaming service simultaneously. In this paper, we address that improving the whole video streaming quality should start from the key concept of scheduling minimum number of low resolution segments iteratively. We define an M-Low optimisation problem and propose a novel M-Low scheduling algorithm, which adjusts the video resolution and optimises the QoE indices in a DASH streaming service. Moreover, we show through simulations that our proposed MLow scheduling achieves a higher QoE measures than those of previously published algorithms.